Evaluating the social orientation of the integrated child development service programme - Borooah, Vani K.; Sabharwal, Nidhi Sadana; Diwakar, Dilip (2014)
Evaluating the Social Orientation of the integrated child development services programme Examining who the beneficiaries are of the Integrated Child Development Services programme, an aspect that has been neglected, this paper presents econometric estimates regarding the relative strength of personal and household circumstances in determining the likelihood of utilising the programme's services. These estimates suggest that inter-group differences in utilisation rates have less to do with characteristics and much more to do with group identity. The paper also suggests a trade-off between quality and utilisation by hypothesising that the poor quality of services leads upper-caste mothers to exit the CDS market and seek these services elsewhere. - Reproduced.
Keywords: Child development; Child welfare